The Impact of Transformation of Social Assistance on Financial Inclusion and Welfare of Beneficiary Families - Arief Fajar Firmansyah; Suharno Suharno; Arintoko Arintoko (Jurusan Ilmu Ekonomi dan Studi Pembangunan Universitas Jenderal Soedirman, 2021)
This study is based on the transformation of the distribution of cash social assistance into non-cash in the City of Tegal. The non-cash distribution is by using a banking account that has a combo card facility, which is a multi-function card that can be used as an ATM card as well as disbursement of social assistance. There is a slice of the objectives of the non-cash transaction referred to as an alternative to accelerate the increase in financial inclusion of the Indonesian population as stated in the National Strategy for Financial Inclusion with the financial inclusion index indicator. This study aims to determine the impact of the transformation of the distribution of social assistance on financial inclusion in Tegal City and the welfare of beneficiary families (KPM). Primary data were collected from questionnaires that have been filled in by KPM and secondary data were obtained from the Central Bureau of Statistics and the Representative Office of Bank Indonesia Tegal. The analytical tool used is a quantitative approach to KPM's response to the distribution of non-cash social assistance. As supporting data, in the problem of financial inclusion, analysis tools are used by qualitatively comparing financial inclusion that is generated as a result of the implementation of the distribution of non-cash social assistance to existing financial inclusion. The analysis shows that the acceptance and perception of KPM supports the transformation of non-cash social assistance distribution, this is supported by KPM's interest in using combo cards as a means of saving. On the other hand, the transformation of the distribution of social assistance to non-cash contributes to financial inclusion in the city of Tegal, namely the Agent Laku Pandai (LKD) contributing 75.20% to banking financial services in Tegal City. From the 4 Welfare Indicator Classifications, it is found that the welfare of KPM has experienced changes in welfare after receiving non-cash social assistance and has improved the welfare of the beneficiary community (KPM).Keywords : Non-Cash Social Assistance, PKH, BPNT